2011
DOI: 10.1093/icesjms/fsr054
|View full text |Cite
|
Sign up to set email alerts
|

The status of routine fishery data collection in Southeast Asia, central America, the South Pacific, and West Africa, with special reference to small-scale fisheries

Abstract: de Graaf, G. J., Grainger, R. J. R., Westlund, L., Willmann, R., Mills, D., Kelleher, K., and Koranteng, K. 2011. The status of routine fishery data collection in Southeast Asia, central America, the South Pacific, and West Africa, with special reference to small-scale fisheries. – ICES Journal of Marine Science, 68: 1743–1750. The Food and Agriculture Organization (FAO) strategy for improving information on the status and trends of capture fisheries (FAO Strategy STF) was endorsed by Member States and the UN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…In spite of long lasting importance of fish to ensure food security of human populations (Bené et al, 2015(Bené et al, , 2016Mcclanahan et al, 2015), few studies have shown a link of fish species consumption to food security. Small-scale fisheries (SSFs) ensure income for millions of people worldwide, especially in developing countries (Andrew et al, 2007;De Graaf et al, 2011). In such countries, while fishing may not guarantee large cash incomes, it helps prevent livelihoods of deprivation and poverty (Bené, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of long lasting importance of fish to ensure food security of human populations (Bené et al, 2015(Bené et al, , 2016Mcclanahan et al, 2015), few studies have shown a link of fish species consumption to food security. Small-scale fisheries (SSFs) ensure income for millions of people worldwide, especially in developing countries (Andrew et al, 2007;De Graaf et al, 2011). In such countries, while fishing may not guarantee large cash incomes, it helps prevent livelihoods of deprivation and poverty (Bené, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Historically, SSFs have been geographically, economically, socially, and politically marginalized and have played practically no role in the development of fisheries science (and vice versa) (69). SSF diversity challenges state capacity to collect and generate landing statistics, and self-reported catch data, often linked to taxable income and/or quota allocation, suffer from under-and overreporting (70). Similar challenges constrain the quality and availability of social science data, making SSFs generally data poor.…”
Section: Food Productionmentioning
confidence: 99%
“…In data‐poor SSFs, fishery‐dependent data collection systems are unlikely to be automated, standardized or centralized, resulting in a general lack of coverage in global fishery data repositories such as the FAO (Chuenpagdee, Liguori, Palomares, & Pauly, ; de Graaf et al., ; Pauly & Zeller, ; Salas, Chuenpagdee, Seijo, & Charles, ). Information about historical catches and trends within a given SSF may instead be transferred via local knowledge, which can be difficult to standardize and translate into quantitative measures or management actions (Hind, ).…”
Section: Conventional Fishery‐dependent Data Systemsmentioning
confidence: 99%
“…Information about historical catches and trends within a given SSF may instead be transferred via local knowledge, which can be difficult to standardize and translate into quantitative measures or management actions (Hind, ). Insufficient resources for data collection and ineffective data collection systems have resulted in a paucity of basic indicator data including total catch, number of vessels and CPUE for many of the world's SSFs, including large regional data gaps for all SSFs in the South Pacific, central America and West Africa (de Graaf et al., ). Where landings data do exist, it may be reported as total landings of all catch rather than landings by species (de Graaf et al., ), which may be useful for understanding regional trends in catches and food security, but may not be effective at guiding stock assessments and management interventions.…”
Section: Conventional Fishery‐dependent Data Systemsmentioning
confidence: 99%